Sociological Study of The Civil Rights of Extramarital Children Towards Biological Fathers Post Constitutional Court Decision No. 46/PUU-VIII/2010 - Dewi, Riza Kusuma Pramastya; Suryadi, Suryadi; Zuliyah, Siti (Literasi Hukum, 2023)
The sociological legal study provides meaning that it examines the nature of humans or human interactions as legal subjects in relation to the law, as well as investigates legal norms. The Sociological Study on Extra-Marital Child's Rights to their Biological Father after the Constitutional Court of Indonesia Decision No. 46/PUU-VIII/2010, examines the legal sociology of recognizing the biological father in light of this decision. Recognition in civil matters for the biological father cannot be enforced, except in cases where it is compulsory under criminal law, as stipulated in Article 280 and 287 of the Civil Code (BW). The rights of Extra-Marital Children (EMC) protected by the Constitutional Court's decision have altered the norm of Article 43(1) of the Marriage Law (UUP) and the law in action regarding the proof of biological paternity. The purpose of this research is to sociologically examine the rights of extra-marital children regarding their biological father after the Constitutional Court's decision, particularly in proving the blood relationship between the child and their biological father based on the Constitutional Court's decision, thereby ensuring the children's civil rights. This research employs a normative-sociological research method, as well as primary and secondary legal materials to support research credibility. The Sociological Study on Extra-Marital Child's Rights after the Constitutional Court's decision faces challenges in its sociological application. In this study, legal sociology only amends the legal norm of Article 43(1) of the Marriage Law as per the Constitutional Court's decision, while the enforceability of proving the civil rights of the biological father cannot be automatically imposed.